2015
DOI: 10.1016/j.taap.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to 50 parts-per-billion arsenic influences histone modifications and associated epigenetic machinery in a region- and sex-specific manner in the adult mouse brain

Abstract: Epidemiological studies report that arsenic exposure via drinking water adversely impacts cognitive development in children and, in adults, can lead to greater psychiatric disease susceptibility, among other conditions. While it is known that arsenic toxicity alters the epigenome, very few studies have investigated its effects on chromatin architecture in the brain. We have previously demonstrated that exposure to a low level of arsenic (50 ppb) during all three trimesters of fetal/neonatal development induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 64 publications
2
43
4
Order By: Relevance
“…The catalytic domain RD2 of the protein REST interacts with CoREST, the main co-repressor of the REST/NRSF complex, that binds to the RE-1 element in neuron-specific genes; additionally, CoREST requires chromatin modifying proteins that we found are impacted by perinatal arsenic exposure in the adult brain [59]. We assessed mRNA expression of Rcor1 , the CoREST gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The catalytic domain RD2 of the protein REST interacts with CoREST, the main co-repressor of the REST/NRSF complex, that binds to the RE-1 element in neuron-specific genes; additionally, CoREST requires chromatin modifying proteins that we found are impacted by perinatal arsenic exposure in the adult brain [59]. We assessed mRNA expression of Rcor1 , the CoREST gene.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that perinatal arsenic exposure alters the epigenetic programs that control the highly orchestrated processes of adult neurogenesis leading to deficits in differentiation of adult NSCs and aberrant stress responses in the hippocampus [5961]. However, while we have determined dysregulation of glucocorticoid signaling in the embryonic brain in response to prenatal arsenic [7], its effect on regulation of embryonic neurogenesis has not been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shift in the global H3K4 methylation status occurs quickly; exposing cells to 1 μM iAs led to the changes in H3K4 methylation states in as little as 24 h (50). Furthermore, Tyler et al found that perinatal arsenic exposure resulted in changes to H3K9Ac and H3K4me3 levels in the brains of adult mice (56,57).…”
Section: Histone Modificationsmentioning
confidence: 99%